SLE during pregnancy, maternal and perinatal outcome in teritary hospital - Leelavathi, .; D. H., Nayana; Kondareddy, Triveni; S., Kaytri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: SLE is an autoimmune disease most frequently found in women of child bearing age and may coexist with pregnancy. Its multisystem involvement and therapeutic interventions pose a high risk for both the mother and the foetus. Disease flares in pregnancy pose challenges with respect to distinguishing physiologic changes related to pregnancy from disease related manifestations. The present study analyzes the fetomaternal outcome of pregnant women with SLE. Methods: An analysis of fetomaternal outcome of pregnant women with SLE during April 2015 to May 2016 at JSS hospital. Results: During the period from April 2016 to May 2016, 3773 deliveries were conducted in the department. Eleven pregnant women with SLE were followed up during this period, giving an incidence of 0.29/1000 deliveries. A high rate of lupus flare during pregnancy was found in the current study. Even among women in remission for more than six months before pregnancy, the rate of lupus flare was not low (27%). Also other complications seen were pre-eclampsia 54.54%, HELLP syndrome in 9.09% , PPH in 50%, polyserositis seen in 9.09% and one maternal death was seen (9.09%). No neonate suffered from heart-blocker however there was 75 % NICU admissions among live borns. Conclusions: Advancing technology and better understanding of the maternal-foetal relationship in lupus have improved outcomes in lupus pregnancies over the last decade. The multisystem nature of the disease, the severity of the organ involvement needs to be assessed and a multidisciplinary approach is required for its diagnosis and successful management.